Implementasi Metode Smart Untuk Penetapan Ranking Siswa Menggunakan Php Dan Mysql - Agung Prabowo; Rozali Toyib (Jurnal Media Infotama, 2022)
By looking at student achievement, the educator in evaluating whether the teaching system used has been successfully accepted or not by the students being taught. Online learning media using a technology approach that is more appropriate to today's student learning systems than the conservative method of learning in class. In addition to class ranking positions, there are also student positions in the Parallel Class Ranking (RKP). The list of RKP positions contains the names of students, sorted by the highest total score for each grade level and announced on the school bulletin board. The Simple Multi Attribute Rating Technique (SMART) method is a multi-criteria decision-making method based on the theory that each alternative consists of a number of criteria that have a value and each criterion has a weight to describe how important its value is compared to other criteria. So the problem is how to implement the smart method for ranking. With the aim of providing student ranking information using the smart method (simple multi attribute rating technique) based on student assessments. It is hoped that this implementation can become a reference not only for stone sales decisions based on rankings but can apply online and structured assessments.